L’efficacité du jeu « Word Jumble Race » pour améliorer la production écrite des étudiants de la section française de UNIMED - Dayuni Agustina; Abdul Ghofur (Universitas Negeri Semarang, 2025)
This study aims to determine the effectiveness of the game ‘Word Jumble Race’ in improving students’ written production in the French Section of UNIMED. The problem is that fourth-semester A students have difficulty writing sentences in the French past tense. This is justified by the results of the pre-test, which show that the average score is 51. According to teacher interviews, this problem is due to a lack of learning resources. The research method used was a single-group pre-test-post-test experimental model. The sampling technique was purposive sampling. The implementation procedure included a pre-test, treatment, and post-test. The pre-test was conducted to determine the students’ initial skills by asking them to write sentences in the French passé composé tense. The treatment was done by teaching the game Word Jumble Race, using simple questions and answers type DELF A1. After a series of research studies, a significant improvement in the students’ learning outcomes was achieved. The average score of 51 in the pre-test rose to 87 in the post-test. The N-gain test was carried out to determine the game’s effectiveness. The result is that the average learning score of 73% falls into the ‘very effective’ category. The game is therefore very effective in improving the ability to write sentences in the French past tense for fourth-semester students at UNIMED.